Do Markets Care About Central Bank Governor Changes? Evidence from Emerging Markets - Moser, Christoph; Dreher, Axel (Journal of Money, Credit and Banking, 2010)
Based on a new daily data set for 20 emerging markets over the period 1992–2006, we examine the reactions of foreign exchange markets, domestic stock markets, and sovereign bond spreads to central bank governor changes. We find that the replacement of a central bank governor negatively affects financial markets on the announcement day, which is in line with the hypothesis that newly appointed central bank governors suffer from a systematic credibility problem at the beginning of their tenure. We also find some evidence that changes in perceived central bank independence affect market

Explaining IMF Lending Decisions after the Cold War - Moser, Christoph; Sturm, Jan-Egbert (Review of International Organizations, 2011)
This paper empirically investigates the economic and political factors that affect a country’s likelihood to sign an arrangement with the IMF and the determinants of the financial size of such a program. Arguably the world and the global financial architecture underwent structural changes after the ending of Cold War and so did the role of the IMF. Hence, we update and extend the work of Sturm et al. (Economics and Politics 17: 177–213, 2005) by employing a panel model for 165 countries that focuses on the post-Cold War era, i.e., 1990–2009. Our results, based on extreme bounds analysis, suggest that some economic and political variables are robustly related to these two dimensions of IMF program decisions. Furthermore, we show that it is important to distinguish between concessional and non-concessional IMF loan

Exporting and Offshoring with Monopsonistic Competition - Egger, Hartmut; Kreickemeier, Udo; Moser, Christoph; Wrona, Jens (Economic Journal, 2022)
We develop a model of international trade with a monopsonistically competitive labour market in which firms employ skilled labour for headquarter tasks and unskilled workers to conduct a continuum of production tasks. Firms can enter foreign markets through exporting and through offshoring, and we show that due to monopsonistic competition our model makes sharply different predictions, both at the firm level and at the aggregate level, about the respective effects of the export of goods and the offshoring of tasks. At the firm-level, exporting leads to higher wages and employment, while offshoring of production tasks reduces the wages paid to unskilled workers as well as their domestic employment. At the aggregate level, trade in goods is unambiguously welfare increasing since domestic resources are reallocated to large firms with high productivity, and firms with low productivities exit the market. This reduces the monopsony distortion present in autarky, where firms restrict employment to keep wages low, resulting in too many firms that are on average too small. Offshoring on the other hand gives firms additional scope for exercising their monopsony power by reducing their domestic size, and as a consequence the resources spent on it can be wasteful from a social planner’s point of view, leading to a welfare loss

Exporting, Skills and Wage Inequality - Moser, Christoph; Urban, Dieter; Klein, Michael W. (Labour Economics, 2013)
International trade has been cited as a source of widening wage inequality in industrial nations. Most previous empirical evidence supports this claim by showing an effect in which increasing exports tilt demand towards firms which export and employ a relatively large proportion of higher-skilled workers from the group of firms which do not export. We find that, in addition to this, there is also an effect whereby, among exporting firms, there is a significant wage premium for high-skilled workers and a wage discount for low-skilled workers. These estimates are based on a matched employer–employee data set of western German manufacturing firms over the period 1993–2007. Our estimates suggest that export activity can be associated with up to 30% of within and between skill group wage inequalit

Hidden protectionism? Evidence from non-tariff barriers to trade in the United States - Grundke, Robert; Moser, Christoph (Journal of International Economics, 2019)
Can the enforcement of product standards be protectionism in disguise? This paper estimates the costs of non-compliance with U.S. product standards, using a new database on U.S. import refusals from 2002 to 2014. We find that import refusals decrease exports to the United States. This trade reducing effect is driven by developing countries and by refusals without any product sample analysis, in particular during the Subprime Crisis and its aftermath. We also provide evidence that given product standards were enforced more strictly during the crisis while the quality of imported products did not deteriorate. These results are consistent with the existence of counter-cyclical, hidden protectionism due to non-tariff barriers to trade in the United States. (C) 2019 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2019-04-18

International Competitiveness, Job Creation and Job Destruction - An Establishment-level Study of German Job Flows - Moser, Christoph; Urban, Dieter; Weder di Mauro, Beatrice (Journal of International Economics, 2010)
This study investigates the impact of international competitiveness on net employment, job creation, job destruction, and gross job flows for a representative sample of German establishments from 1993 to 2005. We find a statistically significant but economically small effect of real exchange rate shocks on employment, comparable to the one found in studies for the United States. However, contrary to the United States, the employment adjustment (among surviving firms) operates mainly through the job creation rather than the job destruction rate. Job destruction occurs essentially through discrete events such as restructuring, outsourcing and bankruptcy. We suggest that these findings are consistent with a highly regulated labor market, in which smooth adjustment is costly and possibly delaye

Offshoring and Job Polarisation between Firms - Egger, Hartmut; Kreickemeier, Udo; Moser, Christoph; Wrona, Jens (2016)

Offshoring and job polarisation between firms - Egger, Hartmut; Kreickemeier, Udo; Moser, Christoph; Wrona, Jens (Journal of International Economics, 2024)
Using linked employer–employee data for Germany, we provide evidence for job polarisation between firms and identify offshoring as an important determinant of these employment changes. To accommodate these findings, we set up a model in which offshoring to a low-wage country can lead to job polarisation in the high-wage country due to a reallocation of labour across firms that differ in productivity and pay wages that are positively linked to their profits. Offshoring is chosen only by the most productive firms, and only for those tasks with the lowest variable offshoring costs. A reduction in those variable costs increases offshoring at the intensive and at the extensive margin. Well in line with our evidence, this causes domestic employment shifts from the newly offshoring firms in the middle of the productivity distribution to firms at the tails of this distribution, paying either very low or very high wages.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Heterogeneous firms; Job polarisation; Offshoring; Unemployment

On the Heterogeneous Employment Effects of Offshoring - Identifying Productivity and Downsizing Effects - Moser, Christoph; Urban, Dieter; Weder di Mauro, Beatrice (Economic Inquiry, 2015)
This article examines the channels through which offshoring affects employment in a representative sample of German establishments, using a difference-in-differences matching approach. Offshoring is measured by an increase in the share of foreign to total intermediate inputs at the plant-level. We identify a positive productivity effect and isolate a negative downsizing effect from offshoring on employment, by exploiting differences between offshoring plants that do and do not simultaneously restructure. Furthermore, we cannot find evidence of negative indirect employment effects on domestic suppliers or competitor

Political Risk and Export Promotion: Evidence from Germany - Moser, Christoph; Nestmann, Thorsten; Wedow, Michael (World Economy, 2008)
Political risk represents an important hidden transaction cost that reduces international trade. This paper investigates the claim that public export credit guarantees mitigate this friction to trade flows and hence promote exports. We employ an empirical trade gravity model, where we explicitly control for political risk in the importing country in order to evaluate the effect of export guarantees. Using a novel data set on guarantees, we estimate the effect of guarantees in a static and dynamic panel model. We find a statistically and economically significant positive effect of public export guarantees on exports which indicates that export promotion is indeed effective. Furthermore, political risk turns out to be an important obstacle for exports and hence should be taken into account in any empirical model of trad

The European Commission and the revolving door - Luechinger, Simon; Moser, Christoph (European Economic Review, 2020)
Decisions of the EU Commission have important consequences for the corporate sector. Thus, the fact that scores of ex-Commissioners go through the revolving door to work for companies raises concerns. Many suspect companies of profiting from privileged access to information and key decision-makers. We assess whether companies do indeed profit from hiring ex-Commissioners. Based on a unique dataset of all Commissioners who served in the Commissions of Jacques Delors I to Jose Manuel Barroso II spanning over 29 years, we look at stock market responses to announcements of such hirings. We find positive abnormal returns, which implies that investors anticipate benefits to companies. The reactions are larger for hirings in the first two years after a former Commissioner left office, when connections and insider knowledge are still fresh. (C) 2020 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2020-08-07
Keywords: Diskriminierung

The exporter wage premium when firms and workers are heterogeneous - Egger, Hartmut; Egger, Peter; Kreickemeier, Udo; Moser, Christoph (European Economic Review, 2020)
In this paper, we develop a new model of international trade, in which workers featuring higher innate abilities match with firms featuring higher innate productivities. This model allows us to quantify the effect of trade on labour income inequality when workers have heterogeneous abilities within the broad groups of skilled and unskilled workers. Self-selection of the most productive firms into exporting generates an exporter wage premium, and our framework with skilled and unskilled workers allows us to decompose this premium into its skill-specific components. We employ linked employer-employee data from Germany to structurally estimate the parameters of the model. These parameter estimates imply an average exporter wage premium of 6 percent, with exporting firms paying no wage premium at all to their unskilled workers, while the premium for skilled workers is 15 percent. Measured by the Theil index, moving the economy to autarky would reduce wage inequality within the group of skilled workers by 29 percent, and it would reduce overall labour income inequality by 8 percent.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Ability differences of workers; Exporter wage premium; Heterogeneous firms; Trade and wage inequality

The political economy of the European Union - Duer, Andreas; Moser, Christoph; Spilker, Gabriele (Review of International Organizations, 2020)
CRIS-Team WoS Importer:2020-06-05

The Revolving Door Phenomenon - Luechinger, Simon; Moser, Christoph (The Political Economy of Lobbying, 2023)
The revolving door is a widespread phenomenon. Job transitions between the public and private sectors occur in both directions. They are prevalent in many countries, have gained in importance over time, and affect many firms and individuals. This chapter discusses potential negative and positive consequences of the revolving door—both from the perspective of firms and individuals in question and from society at large. The empirical literature suggests that job transitions between sectors are beneficial for the firms and individuals involved. While there is little research on potential socially desirable effects of the revolving door, there is evidence for substantial negative effects.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Conflicts of interest; Corruption; Political connections; Revolving door

The Value of the Revolving Door: Political Appointees and the Stock Market - Lüchinger, Simon; Moser, Christoph (Journal of Public Economics, 2014)
We analyze stock market reactions to announcements of political appointments from the private sector and corporate appointments of former government officials. Using unique data on corporate affiliations and announcements of all Senate-confirmed U.S. Defense Department appointees of six administrations, we find positive abnormal returns for political appointments. These estimates are not driven by important observations, volatile stocks, industry-wide developments or the omission of further commonly used return predictors. Placebo events for close competitors and alternative dates yield no effects. Effects are larger for top government positions and less anticipated announcements. We also find positive abnormal returns for corporate appointments and positive effects of political connections on procurement volume. Our results suggest that concerns over conflicts of interest created by the revolving door seem justified, even in a country with strong institution

Who Benefits from Regional Trade Agreements? - Moser, Christoph; Rose, Andrew K. (European Economic Review, 2014)
The consequences of regional trade agreements (RTAs) on countries׳ welfare are disputed. In this paper, we assess these effects using stock returns from a recent data set that spans over 200 RTA announcements, 80 economies, and 20 years. We measure the effects of news concerning RTAs on the returns of national stock markets, after adjusting these returns for international stock market movements. We then link these abnormal returns to features of the RTA members and the agreements themselves. We find strong evidence of the natural trading partner hypothesis; stock markets rise more when RTAs are signed between countries that already engage in high volumes of trade. Stock markets also rise more when poorer countries sign RTAs, and when RTAs are signed with smaller partners. We also find no evidence that capital markets expect significant trade diversion effect

Why Do Trade Negotiations Take So Long? - Moser, Christoph; Rose, Andrew K. (Journal of Economic Integration, 2012)
The Doha multilateral round of trade negotiations sponsored by the WTO has been dragging on for over a decade, with no end in sight. In this short paper we assess empirically what determines the duration of trade negotiations, focusing on the span between the start of trade talks and their conclusion. We use data from 88 regional trade agreements between 1988 and 2009, and a semi-parametric Cox proportional hazards model. Four factors are robust determinants of the length of RTA negotiations. Negotiations are more protracted when there are more countries at the negotiation table, and when the countries are not from the same region. Negotiations between more open and richer countries also finish more quickl